61 hours a Reacher novel - Child, Lee (New York Dell, 2010)
Reacher arrives accidentally in a small South Dakota town, where during a dangerous winter storm he is enlisted to protect a lone witness who local police hope can help convict a brutal crime ring.
Keywords: Reacher, Jack (Fictitious character) -- Fiction; Retired military personnel -- Fiction; Witnesses -- Protection -- Fiction; Assassins -- Fiction; Winter storms -- Fiction